Patient‐reported outcomes in patients co‐infected with hepatitis C virus and human immunodeficiency virus treated with sofosbuvir and velpatasvir: The ASTRAL‐5 study. (25th May 2017) - Younossi, Zobair M.; Stepanova, Maria; Sulkowski, Mark; Wyles, David; Kottilil, Shyam; Hunt, Sharon
Abstract: Background & Aim: The fixed‐dose combination of sofosbuvir and velpatasvir (SOF/VEL) is a ribavirin‐free pan‐genotypic regimen with high efficacy. We assessed the impact of SOF/VEL on patient‐reported outcomes (PRO) of HIV‐HCV co‐infected patients. Methods: HIV‐HCV co‐infected patients were treated with 12 weeks of SOF/VEL (400 mg/100 mg daily). All subjects completed four PRO questionnaires [CLDQ‐HCV, SF‐36, FACIT‐F and WPAI:SHP] before, during and post‐treatment. Results: ASTRAL‐5 enrolled 106 HIV‐HCV co‐infected patients on stable antiretroviral therapy (age: 54.2±0.9 years, cirrhosis: 17.9%, HCV genotype 1: 73.6%). SVR‐12 was achieved by 95.3% of subjects. By week 4 of treatment, PRO scores improved from the baselines levels in 12 out of 26 calculated PRO domains (on average, +1.9 to +7.4 points on a universal 0‐100 PRO scale, all P <.05). By the end of treatment, improvements were seen in 20/26 PRO domains (+2.5% to +11.9%, P <.03). There were no significant decrements in any PRO domains during treatment. By follow‐up week 12, patients who achieved SVR‐12 experienced significant improvement in 19/26 of their PRO domains (+3.2% to +13.3%, P <.05). After controlling for baseline psychiatric co‐morbidities, improvements in PRO scores during treatment with SOF/VEL were similar to those seen in matched HCV‐mono‐infected patients treated with the same regimen (ASTRAL‐1 study). In multivariate analysis, pre‐treatment anxiety and concomitant use of opioids were the most consistent significant ( P <.05) predictors of PRO impairment in HIV‐HCV patients. Conclusions: Patients with HIV‐HCV treated with SOF/VEL experience very high efficacy accompanied by early and sustained improvement of patient‐reported outcomes covering all aspects of patients' experience.